Imaging methods for the local lymphatic system of the axilla in early breast cancer in patients qualified for sentinel lymph node biopsy - Nowikiewicz, Tomasz; Kurylcio, Andrzej; Polkowski, Wojciech; Zegarski, Wojciech (Menopause Review/Przegląd Menopauzalny, 2016)
Breast cancer is the most common malignancy in women in well-developed countries. Despite a constant increase in its incidence, the percentage of patients diagnosed with the disease in the non-invasive stage is also rising. This allows more frequently for the use of breast-preserving surgical techniques, involving the breast and the regional lymphatic system. According to current guidelines of expert panels and research societies, the recommended method of identifying the sentinel lymph node is the use of an isotope marker with a dye (a combined isotope and dye method). Cooperation with a nuclear medicine unit is essential (performing a preoperative lymphoscintigraphic scan to identify the lymphatic drainage basin and sentinel lymph node). In the case of smaller centers treating breast cancer, it can be associated with a number of difficulties, including organizational ones, and also increasing general treatment costs. A possible solution to these problems is to use alternative techniques of visualizing the sentinel lymph node, which do not require a radiotracer. In this paper we discuss the currently available methods of mapping the lymphatic system of the axillary region in patients with early breast cancer. The review is limited to reporting on methods of proven (based on clinical research) high diagnostic value.